2007
DOI: 10.1016/j.otohns.2007.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms Underestimated in Vertiginous Patients

Abstract: Nearly 20% of vertiginous patients also have depressive symptoms. Assessment of psychiatric and psychosomatic symptoms should accompany neuro-otologic evaluation to achieve the best treatment strategy and prevent chronic outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 20 publications
3
27
0
Order By: Relevance
“…Using the Hospital Anxiety and Depression Scale (HADS), one study from the UK found that 17% of dizzy and vertiginous patients were depressed, and 29% were anxious 34. Another study conducted in Finland using the Beck Depression Inventory (BDI) found that 19% of patients with vertigo were depressed 35. The population-based study in Germany, discussed previously, found a 17% prevalence of self-reported depression in the past year among individuals with vestibular vertigo.…”
Section: Discussionmentioning
confidence: 93%
“…Using the Hospital Anxiety and Depression Scale (HADS), one study from the UK found that 17% of dizzy and vertiginous patients were depressed, and 29% were anxious 34. Another study conducted in Finland using the Beck Depression Inventory (BDI) found that 19% of patients with vertigo were depressed 35. The population-based study in Germany, discussed previously, found a 17% prevalence of self-reported depression in the past year among individuals with vestibular vertigo.…”
Section: Discussionmentioning
confidence: 93%
“…Garcia, et al [17] observed a psychological manifestation in 63.4% of vertigo patients and diagnosed as panic disorder, depressive disorder, anxiety disorder. Also Grunfeld, et al [18] and Ketola, et al [19] reported that over the 45% patients who have dizziness could be classified as depressed or anxious based on the self-reported instruments.…”
Section: Discussionmentioning
confidence: 99%
“…59 Our study documented frequent cranial nerve palsies in patients with chordoma, and the most common was diplopia. Neurological symptoms such as headache, 63 diplopia, 33 and dizziness 31,39 that are common in patients with skull base chordomas have been associated with anxiety and depression. We did not observe an association between cranial nerve deficit and depression as measured by PHQ-9 score.…”
Section: Discussionmentioning
confidence: 99%